2014
DOI: 10.1186/1742-4690-11-39
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to simian immunodeficiency virus low dose rectal challenge is associated with higher constitutive TRIM5α expression in PBMC

Abstract: BackgroundAt least six host-encoded restriction factors (RFs), APOBEC3G, TRIM5α, tetherin, SAMHD1, schlafen 11, and Mx2 have now been shown to inhibit HIV and/or SIV replication in vitro. To determine their role in vivo in the resistance of macaques to mucosally-acquired SIV, we quantified both pre-exposure (basal) and post-exposure mRNA levels of these RFs, Mx1, and IFNγ in PBMC, lymph nodes, and duodenum of rhesus macaques undergoing weekly low dose rectal exposures to the primary isolate, SIV/DeltaB670.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…One possible reason for this discrepancy is that IFN-alpha in plasma becomes undetectable by ELISA in the chronic phase of the infection and is therefore less sensitive for determining the interferon response [ 65 ] than measuring ISG like MX1 as in our work or ISG15 [ 36 ]. In agreement with results from present study, Aamer and colleagues also observed a maximum BST2 and MX1 expression during acute infection [ 66 ]. Strong induction of BST2 together with other restriction factors has also been observed in vivo after treatment of HIV/HCV-coinfected patients with pegylated IFN-alpha/ribavirin (IFN-alpha/riba) exhibiting a good correlation with ISG15 [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…One possible reason for this discrepancy is that IFN-alpha in plasma becomes undetectable by ELISA in the chronic phase of the infection and is therefore less sensitive for determining the interferon response [ 65 ] than measuring ISG like MX1 as in our work or ISG15 [ 36 ]. In agreement with results from present study, Aamer and colleagues also observed a maximum BST2 and MX1 expression during acute infection [ 66 ]. Strong induction of BST2 together with other restriction factors has also been observed in vivo after treatment of HIV/HCV-coinfected patients with pegylated IFN-alpha/ribavirin (IFN-alpha/riba) exhibiting a good correlation with ISG15 [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is not unusual, since studies of other ISGs demonstrate that even basal expression of ISGs still possess certain antiviral activity. For example, the high basal expression of an ISG, TRIM5α, in peripheral blood mononuclear cells (PBMCs) dramatically restricts mucosal transmission of simian immunodeficiency virus (SIV) more efficiently than when induced with type I IFN [30]. Certain host genes, including recently discovered tyrosine kinase nonreceptor 1 (TNK1), are required for maintenance of basal ISG expression [31].…”
Section: Discussionmentioning
confidence: 99%